Research ethics in the Human and Social Sciences: divergences and convergences in data processing (Práxis Educativa, 2023)
This article analyzes the divergences and convergences on the treatment of research data and the investigative field of Human and Social Sciences, in Resolution no. 466/2012, in Resolution no. 510/2016 and the General Data Protection Law (LGPD). This is a documentary investigation, with a qualitative approach and exploratory objective, based on the understanding of the theorists De La Fare, Carvalho and Pereira (2017), Mainardes (2017) and Peixoto (2017). The results indicate: i) the lack of determinants linked to human integrity; ii) the lack of autonomy of the research subject; iii) the need to modernize data processing resolutions; iv) the need for the researched subject to access the investigation results, as well as the transparency of access to his/her data; v) the need to fertilize teaching and an ethical culture in educational institutions.Keywords: Ethics in Research. Human and Social Sciences. Procedures.